Neonatal MK-801 treatment differentially alters the effect of adolescent or adult MK-801 challenge on locomotion and PPI in male and female rats. (September 2013) - Zhao, Ying-Ying; Li, Ji-Tao; Wang, Xiao-Dong; Li, You-Hong; Huang, Run-Hu; Su, Yun-Ai; Si, Tian-Mei
Schizophrenia is a neurodevelopmental disorder and is typically "triggered" by subsequent insults in life. The N-methyl-D-aspartate (NMDA) receptor antagonist dizocilpine (MK-801) induces locomotor hyperactivity and prepulse inhibition (PPI) deficits, which can mimic the schizophrenia phenotype. In this experiment, we assessed whether neonatal exposure to MK-801 (postnatal days 5–14) could induce sensitization to both hyperactivity and PPI deficit caused by later-life acute MK-801 treatment during adolescence or adulthood. Our results showed that the hyperactivity induced by an acute MK-801 challenge was enhanced in male and female rats after neonatal MK-801 treatment. Notably, in the PPI test, adult female rats neonatally exposed to MK-801 exhibited a significantly greater reduction in PPI in response to acute MK-801 administration, whereas male rats receiving neonatal MK-801 treatment expressed attenuated PPI disruption in adulthood. Our data indicate that a combination of neonatal and later-life NMDA receptor blockades could induce sensitization in the locomotor activity of both sexes in adolescence and adulthood. In addition, a sex difference was observed in the effects of this treatment regime on PPI.